2021
DOI: 10.3390/app112110444
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Primary Atomization Characteristics of Sonic Air-Assist Atomizers

Abstract: The present study compares two twin-fluid atomizer concepts based on the airflow (shock waves) pattern obtained through shadowgraph imaging for atomization of water with a low air/water pressure supply. The research work was conducted using the backlight imaging technique for converging (sonic) and converging–diverging (supersonic) air-assist atomizers with a 3.0 mm (throat) diameter. An annular sheet of thicknesses 70 µm and 280 µm with a high-speed air-core was employed to study the breakup dynamics for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Using a CMOS-based Photron SA-Z high-speed camera, shadowgraph imaging was performed at 21,000 frames per second (fps) with a shutter speed of ∼50 µsec. The experimental setup is explained in more detail (Sikka et al 27 ) The schematic diagram for the shadowgraph setup is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Using a CMOS-based Photron SA-Z high-speed camera, shadowgraph imaging was performed at 21,000 frames per second (fps) with a shutter speed of ∼50 µsec. The experimental setup is explained in more detail (Sikka et al 27 ) The schematic diagram for the shadowgraph setup is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%